Propriedades estruturais e de Bulk de cerâmicas dielétricas Ba2BiM5+O6 investigadas utilizando simulações estáticas - Carvalho, Edson Firmino Viana de (2007)
In this work we have performed static atomistic simulations to investigate the structural and bulk properties of the complex double perovskites with rock-salt ordering with the Ba2BiM+5O6 stoichiometry, where M+5 = Ta5+, Sb5+ and Nb5+, under pressure changes. For this we have adopted a Buckingham potential model for the ionic interactions and the shell model in order to model the atomic polarizations. In the case of Ba2BiTaO6 and Ba2BiNbO6 compounds, we assumed potential parameters listed in the literature and in the case of Ba2BiSbO6 compound, new potential parameters for the Sb5+¡O interaction were founded. The results observed with theses potentials for the cases of Ba2BiTaO6 and Ba2BiSbO6 materials, shown that the potential sets are sensitive to the structural phase transition observed experimentally between the phases R¹3 and I2=m at high pressures. Thus it was possible to de ne the critical pressure for Ba2BiSbO6. Some elastic and mechanical properties of these materials had been calculated and had shown these transitions clearly, where it was observed the Young's modulus collapse at the critical pressure and discontinuities in the shear modulus and in the longitudinal and transversal sound propagation speeds. The elastic constants had not presented collapse and the volume practically did not change at the transition, what as expected from the experimental results. For the case of Ba2BiNbO6 material, once that there are not experimental results, the aim was to predict their structural characteristics. There were tested four potential sets presented in the literature using as input initial cell parameters data generated by the SPUDS software. Two of these potential sets exhibited the same phase transition that Ba2BiTaO6 and Ba2BiSbO6 present.